Ele é a nossa paz : a eclesiologia ecumênica de Ef 2,11-22 - Baquer, Vinicius Pimentel (2023)
This master’s thesis addresses the theme of ecumenical ecclesiology present in the pericope of Eph 2,11-22, made possible by the work of pacification that Jesus Christ performs through his sacrifice on the Cross. To this end, we started with a general analysis of the Letter to the Ephesians, questions of authorship and pseudoepigraphy, as well as the main theological insights of the Letter to, finally, propose an analysis of the structure of the pericope, highlighting the lexical and semantic parallels that make up the pericope plot. The chiasmic structure evidences the sacrificial death of Jesus Christ, which abolishes the Law, as the foundation of the unity of Jews and Gentiles in the new humanity, which is the image of the Church. Peace is the fruit of the abolition of hostility and can be experienced in communion in the ecclesial community, which generates new citizenship through the common foundation of all the faithful.